POST PANDEMIC OR PRE-PANDEMIC DESIGN IN INDONESIA? - Harsritanto, Bangun i.r. (MODUL, 2021)
Nowadays many papers were published on the topic of the pandemic. Research about pandemics become an urgent and hot issue, since the impact in every country in many aspects. This editorial was trying to find out the narration and analyse the current condition in a design perspective. The result shows that the pandemic topic might be a panic response toward the current condition and after PPKM removal, all things become no pandemic-based design.